A little known civilization [electronic resource] - Deans, James, 1827-1905. ([S.l. : s.n., 1895)
From: The American antiquarian, v. XVII no. 4, July 1895. Caption title. "Read before the British Columbia Natural History Society." Electronic reproduction. Mode of access: Internet. 44